Outcome Analysis of Factors Impacting the Urology Residency Match. Issue 4 (July 2016) - Pagano, Matthew J.; Cooper, Kimberly L.; McKiernan, James M.; Badalato, Gina M.
Abstract : Introduction: : Match outcome studies allow applicants and counselors to adequately prepare and make informed decisions. We sought to characterize predictors of success in URMP (Urology Residency Match Program) using standard application data. Methods: : All residency applications received at our department for the 2015 URMP, representing 56% of the national applicant pool, were prospectively entered in an applicant database. Data pertaining to applicant demographics and academic achievement were collected. Nationally published medical school and urology residency rankings were abstracted into tiers. The primary outcome was successful matching into urology and the secondary outcome was quality of the matched residency by ranking. Logistic and linear univariate and multiple regression modeling was performed to detect associations among all independent and outcome variables. Results: : The final analysis included 244 applicants, of whom 191 (78.3%) successfully matched. On multivariable analysis significant positive predictors included the number of honors grades (p = 0.047, OR 1.4), away subinternships (p = 0.013, OR 1.8) and USMLE (United States Medical Licensing Examination) Step 1 score (median 245 vs 232, p = 0.024). Negative predictors included noncurrent medical school senior status (p = 0.044, OR 0.24) and lower ranked medical school tier (p = 0.003, OR 0.78). Medical school tier (p <0.001), USMLE Step 1 score (p = 0.002) and number of published abstracts (p = 0.042) were predictive of entering a more highly ranked residency program. Conclusions: : Based on an institutional sample of the national applicant cohort we identified multiple independent predictors of URMP outcome. This may be useful for applicant counseling in preparation for the match process, although findings may not be applicable to all candidates.